106 New service: a cardiac physiologist managed exercise stress echo. (5th June 2017) - Singh, Rajender; Kemp, Zoe; Al-Janabi, Firas; Kane, Steven; Coles, Duncan
Abstract : Background: National institute for health and clinical excellence (NICE) recommends functional assessment for patients presenting with chest pain of recent origin (CPRO), who have intermediate probability for coronary heart disease (CAD). Exercise stress echocardiography (SE) is a well established, reliable and safe method for assessment of ischaemic heart disease. The exercise stress ECHO service has traditionally been a consultant cardiologist led service (CCSE). But with increasing pressure of demand and to cut waiting times a cardiac physiologist managed exercise stress echocardiography service (CPSE) was started in May 2014 in a district general hospital, as per the British cardiac society protocol 2003. Patients are usually referred from the chest pain clinic. All requests are screened by a consultant cardiologist and test and reporting performed independently by British Society of Echocardiography accredited experienced senior cardiac physiologist, who has also had departmental assessment with direct consultant supervision and review. The team includes 2 physiologist (1st -sonographer, operator and reporter, 2nd assistant (ECG) and cardiac nurse (BP, Contrast) Methods: A retrospective cohort study comparing data collected from Feb 2013 to March 2014 for consultant led (CCSE) and from May 2014–June 2015 for cardiac physiologist led (CPSE) was performed. Patients with positive stress tests underwent coronary angiography. Patients were followed up from 6–18 months in both groups Results: During the study period there were 172 patients in the CCSE and 162 in the CPSE group. Majority were referred for CPRO (120 vs.108, p=0.5). Image quality was similar in both groups (p=0.20). The number of positive stress test was CCSE 20 vs. CPSE 18 (p=0.09) (Table1). Coronary angiography was performed in 18 patients in both groups, of which 15 had positive tests (Two patients were not investigated further in CCSE group as decision made by consultant for medical management only). Sensitivity and specificity was 73% and 100% in the CCSE vs. 83% and 78% in CPSE group. Territory correlation was similar in both groups. During the follow up period none of the patients with negative test result in the CCSE group had a coronary angiogram, while 9 patients in CPSE group had a coronary angiogram. Of these only 2 were positive and 7 were negative, thus giving a specificity of 78% (Table 2). Conclusion: A cardiac physiologist managed exercise stress echo service (managing and reporting the test independently) has high sensitivity and specificity. It is a safe and effective way to manage patients referred with CPRO. This will help reduce waiting times and improve efficiency of the service. Though, it's hindered by a lack of clinical decision making process on the day, which may warrant further investigation by the non-specialist.